2020
DOI: 10.7759/cureus.10744
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Following Distal Femur Fractures Versus Proximal Femur Fractures in Elderly Population: The Impact of Best Practice Tariff

Abstract: Background and objectives The mortality after hip, proximal femur, fractures in elderly patients has steadily declined in the last decade in the United Kingdom as a result of implementing of multiple protocols focusing on prompt multidisciplinary pre- and post-operative optimization and reducing time to surgery. The pinnacle of these protocols is the development of the best practice tariff as an incentive program for hospitals that meet set criteria by the National Health Service (NHS) England in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…9 10 11 The literature describing distal native femur fractures report 1-year mortality rate between 13.4 and 34.4%; however, these fractures have yet to be compared widely to periprosthetic distal femur fractures. 12 13 Periprosthetic distal femur fracture morbidity and mortality remain ill-defined with few large-scale studies investigating the morbidity and mortality. 14 Furthermore, there are few previous studies comparing the morbidity and mortality to a more well-known entity such as native distal femur fractures.…”
mentioning
confidence: 99%
“…9 10 11 The literature describing distal native femur fractures report 1-year mortality rate between 13.4 and 34.4%; however, these fractures have yet to be compared widely to periprosthetic distal femur fractures. 12 13 Periprosthetic distal femur fracture morbidity and mortality remain ill-defined with few large-scale studies investigating the morbidity and mortality. 14 Furthermore, there are few previous studies comparing the morbidity and mortality to a more well-known entity such as native distal femur fractures.…”
mentioning
confidence: 99%
“…Knowledge of the site distribution of initial and subsequent fragility fractures has clinical implications. Certain fracture sites can be challenging to clinically manage, such as the distal femur, which is associated with heightened mortality rates compared to other fracture sites among the general elderly population ( Mubark et al, 2020 ). The differential risks by fracture site may be exacerbated in adults with CP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with our results, Mubarak et al reported that compared to the mortality rate in the proximal femoral group (6.99% at 30 days, 14.52% at six months, and 21.51% at one year), the distal femoral group was greater at all times (9.68% at 30 days, 20.32% at six months, and 34.41% at one year). Moreover, the same study indicated that a higher number of patients with distal femoral fractures were treated without surgical intervention (15% vs. 4%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%